The race that precedes coactivation: development of multisensory facilitation in children. - Barutchu, A; Crewther, D; Crewther, S (2009)
RATIONALE: The facilitating effect of multisensory integration on motor responses in adults is much larger than predicted by race-models and is in accordance with the idea of coactivation. However, the development of multisensory facilitation of endogenously driven motor processes and its relationship to the development of complex cognitive skills in school-age children is largely unexplored. METHOD: Twenty adults and 95 children where allocated into six age groups: 6, 7, 8, 9, 10-11 and adults. Participants' motor reaction times (MRTs) and accuracy in response to the detection of auditory, visual and audiovisual stimuli were recorded. Children's reading accuracy and nonverbal IQ were also assessed. RESULTS: In general, MRTs of children were significantly slower with greater variability than those of adults. Although the average level of multisensory facilitation was similar for all age groups, mean cumulative density functions (CDFs) showed that multisensory facilitation in 6 and 10-11-year-olds is within the predictive limits of race-models. Where coactivation was seen in the CDF of individual children it was not as strong or as consistent as that in adults. The degree of multisensory facilitation did not correlate with age, reading accuracy or IQ. CONCLUSION: The average level of multisensory facilitation to endogenously driven motor responses does not change gradually with age nor is it related to intelligence or reading accuracy. In general, multisensory integration remains immature until 10-11 years of age and lies within the predicted confines of race-models.